Persistence of Gender Related-Effects on Visuo-Spatial and Verbal Working Memory in Right Brain-Damaged Patients - Piccardi, Laura; Matano, Alessandro; D’Antuono, Giovanni; Marin, Dario; Ciurli, Paola; Incoccia, Chiara; Verde, Paola; Guariglia, Paola (Frontiers in Behavioral Neuroscience, 2016)
The aim of the present study was to verify if gender differences in verbal and visuo-spatial working memory would persist following right cerebral lesions. To pursue our aim we investigated a large sample (n. 346) of right brain-damaged patients and healthy participants (n. 272) for the presence of gender effects in performing Corsi and Digit Test. We also assessed a subgroup of patients (n. 109) for the nature (active vs. passive) of working memory tasks. We tested working memory (WM) administering the Corsi Test (CBT) and the Digit Span (DS) using two different versions: forward (fCBT and fDS), subjects were required to repeat stimuli in the same order that they were presented; and backward (bCBT and bDS), subjects were required to repeat stimuli in the opposite order of presentation. In this way, passive storage and active processing of working memory were assessed. Our results showed the persistence of gender-related effects in spite of the presence of right brain lesions. We found that men outperformed women both in CBT and DS, regardless of active and passive processing of verbal and visuo-spatial stimuli. The presence of visuo-spatial disorders (i.e., hemineglect) can affect the performance on Corsi Test. In our sample men and women were equally affected by hemineglect, therefore it did not mask the gender effect. Generally speaking, the persistence of the men's superiority in visuo-spatial tasks may be interpreted as a protective factor, at least for men, within other life factors such as level of education or kind of profession before retirement.